MGR Hash Functions. Issue 5 (3rd September 2019) - Bussi, Khushboo; Dey, Dhananjoy; Mishra, P. R.; Dass, B. K.
Abstract: GOST-R 34.11-94 is a Russian standard cryptographic hash function that was introduced in 1994 by the Russian Federal Agency for the purposes of information processing, information security, and digital signature. Mendel et al. (2008 ) and Courtois and Mourouzis (2011 ) found attacks on the compression function of the GOST-R structure that were basically weaknesses of the GOST-R block cipher (GOST 28147–89, 1989 ). Hence in 2012, it was updated to GOST-R 34.11-2012, which replaced the older one for all its applications from January 2013. GOST-R 34.11-2012 is based on a modified Merkle-Damgård construction. Here we present a modified version of GOST-R 34.11-2012 (Modified GOST-R (MGR) hash). The design of the MGR hash is based on wide-pipe construction, which is also a modified Merkle-Damgård construction. MGR is much more secure as well as three times faster than GOST-R 34.11-2012. Advanced Encryption Standard (AES)-like block ciphers have been used in designing the compression function of MGR because AES is one of the most efficient and secure block ciphers and has been evaluated for more than 14 years. A detailed statistical analysis with a few other attacks on MGR is incorporated into this paper.